TELAAH TERHADAP PASAL 14 AYAT (1) HURUF B RANCANGAN UNDANG-UNDANG KEPOLISIAN PERUBAHAN KETIGA - A. Tigor Witono; Lucia Rachmawati (LPPM institut Teknologi Bisnis AAS Indonesia, 2024)
Cyberspace communication for every person and community is a right to privacy granted by the 1945 Constitution. The task of Polri's surveillance of Cyberspace Communications contained in article 14, paragraph 1, letter b, has received criticism from the public. The task is considered too wide-ranging to give authority to the police to potentially violate individual privacy rights. This investigation aims to determine whether article 14, paragraph (1) (b), has fulfilled the legal purpose both in terms of justice, finality and legal certainty. This research is normative legal research, with legal approaches and historical approaches, legal materials used as primary and secondary legal materials. Techniques of collection of legal materials with library studies and techniques of deductive legal material analysis. The results of the research show that Article 14 (1) letter b of the Third Amendment Police Bill does not meet the legal objectives because it does not satisfy the aspects of justice, utility and certainty. Furthermore, given that there are guarantees of the rights of individuals enshrined in the Basic Law of equality of rights, the right of communication and the right to personal self-protection that must be fulfilled in proportion, so that Article 14 paragraph (1) letter b of the Draft Third Amendment Police Act does not meet the legal purpose. Keyword : Surveillance, police, legal purposes, cyber space